Learning Cardiac Imaging - Ribes, R.; Kuschnir, P.; Luna, A.; Vilanova, J. C.; Jimenez-Hoyuela, J. M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book is an introduction to cardiac imaging. Written by radiologists, cardiologists, and nuclear medicine physicians in a user-friendly format, it provides the reader with a multidisciplinary selection of the most prevalent cardiac conditions. The book is subdivided into four sections: Cardiac Multislice CT, Echocardiography, Cardiac Magnetic Resonance and Nuclear Cardiology. Each chapter is presented with an introduction to the subspecialty and a selection of cases with illustrations, comments from clinical and radiological standpoints, and bibliographical recommendations.
Cardiac Multislice CT -- Echocardiography -- Cardiac Magnetic Resonance -- Nuclear Cardiology.
Keywords: Medicine; Radiology, Medical; Cardiology; Heart -- Surgery; Medicine & Public Health; Imaging / Radiology; Cardiology; Cardiac Surgery